Anti-tumor effects and cell motility inhibition of the DN604-gemcitabine combined treatment in human bladder cancer models. (1st January 2021) - Wang, Xinyi; Chen, Feihong; Gou, Shaohua
Graphical abstract: Abstract: Bladder cancer is one of the major tumors for men in the world, in which therapy the combination of cisplatin and gemcitabine is still fist-line applied to treat with advanced or metastatic bladder cancer. In our early study, we developed a potential Pt(II) agent, DN604, which has anti-tumor effect as potent as cisplatin toward bladder cancers. Herein, we aim at investigating the combinatory application of DN604 with gemcitabine for bladder cancer treatment. In vitro studies proved that the combined treatment of DN604 and gemcitabine could limit cell proliferation by elevating the incidence of DNA damage induced apoptosis. Notably, further researches showed that the DN604-gemcitabine treatment suppressed cell autophagy to inhibit cell motility upon the ROS dependent p38 MAPK signaling pathway, explicating its better anti-tumor activity than single drug treatment or the cisplatin-gemcitabine treatment. In vivo tests confirmed that the DN604-gemcitabine treatment has superior anti-tumor activity with low toxicity to cisplatin or its combination with gemcitabine treatments. DN604 plus gemcitabine, is of great significance for the treatment with human bladder cancer. Our study has provided a potential combination treatment option.